Pengaruh Kualitas Pelayanan Terhadap Loyalitas Pelanggan Pada Klinik Esther House of Beauty Manado - Irjayanti, Endah; Tampi, Johny R. E.; Mukuan, Danny D. S. (JURNAL ADMINISTRASI BISNIS (JAB), 2018)
The purpose of this research to find determine wheter quality of service that reliability, responsiveness, assurance, emphaty, and tangibles influential throught of customer loyalty in Esther House of Beauty Manado.This type of research is quantitative research with descirptive approach. The population of this research in Esther House of Beauty Manado customers, with 60 respondents. The result of this simultaneous showed that the impact of reliability, responsiveness, assurance, emphaty, tangibles takes controlled of customer loyalty in Esther House of Beauty Manado is 84,5%. Whereas, variable tangibles uninfluenced simultaneously throught loyalty in Esther House of Beauty. Whereas, the result of this research showed that the partial tangiblesÂ  has no influence though customer loyalty in Esther House of Beauty Manado. And the quality variable of service that mostly influence is responsiveness.